Pencarian Rute Terpendek Tim Promosi Kampus dengan Menggunakan Algoritma Genetik - Isnaini Muhandhis; M Shubhan; Hisyam Ib Dani; Arkila Rakasyah; Alven S Ritonga; Mamik Usniyah Sari (Jurnal Teknologi dan Manajemen, 2023)
This research aims to make it easier for the campus marketing team to determine the minimum route when visiting several schools in one day. We develop an optimum route search model using a genetic algorithm. The selection method used is elitist selection and the mutation method used is Reciprocal Exchange Mutation. Mutation probability values were determined at 0.2 and 0.4 with different numbers of individuals. The results of this study, in general, a greater probability of mutation causes a significant change in the arrangement of chromosomes, so that the average fitness result is worse than the probability of a smaller mutation. The number of individuals in the population does not really matter. The best solution obtained is the route 0- 2- 8-7-5-4-9-6-3-1 as far as 73 km.